Low-temperature partitioning extraction optimized for antibiotics quantification in sewage sludge by liquid chromatography-tandem mass spectrometry - Camila Cristina Rodrigues Ferreira da Cunha; Mylena Gomes Freitas; Daniel Aparecido da Silva Rodrigues; André Luis Correa de Barros; Marcelo Carlos Ribeiro; Aline Gomes de Oliveira Paranhos; Sérgio Francisco de; Ananda Lima Sanson; Robson José de Cássia Franco Afonso (Revista Brasileira de Ciências Ambientais)
Antibiotics and their degradation byproducts are a relevant group of contaminants of emerging concern. Conventional wastewater treatment plants fail to remove them. Thus, uncontrolled disposal of antibiotics in the environment increases the spread of antibiotic-resistant bacteria and their genes. The present work describes the development and validation of an analytical method for the simultaneous determination of three antibiotics—sulfamethoxazole (SMX), sulfadiazine (SDZ), and trimethoprim (TMP)—in sewage sludge. The method is based on low-temperature partitioning extraction (LTPE) followed by liquid chromatography-tandem mass spectrometry (LC-MS/MS). LTPE is a low-cost extraction technique that does not require specific equipment, large amounts of solvents and samples, nor longer times to extract antibiotics from sludge. TheLTPE procedure was optimized for dried anaerobic sludge from upflow anaerobic sludge blanket reactors fed with sewage. Theinfluence of sample mass content, ultrasonic bath extraction time, and potential of hydrogen (pH) of the buffer solution on extraction efficiency was evaluated with experimental design methodology. Thebest conditions achieved to extract the target antibiotics were: 150 mg dried sludge, 20min of ultrasonic bath, and pH 7, in addition to 600 μL of McIlvaine buffer solution, and 600 μL organic solvent in one cycle of extraction. The recovery values were 52.7% (SMX), 53.6% (SDZ), and 70.1% (TMP), and the method exhibited good repeatability (≤14.7%). The method detection and quantification limits ranged from 3.6 to 11.3 ng g-1 dw (dry weight) and 11.5 and 36.1 ng g-1 dw, respectively. Sewage sludge samples collected from two municipal wastewater treatment plants in Minas Gerais state/Brazil revealed the presence of TMP (174.2 and 134.8 ng g-1 dw) while sulfonamides were lower than the method detection limit. To the best of our knowledge, this is the first study based on LTPE followed by LC-MS/MS that was applied to simultaneously determine SMX, SDZ, and TMP antibiotics in sewage sludge.